2014
DOI: 10.1063/1.4904717
|View full text |Cite
|
Sign up to set email alerts
|

High 400 °C operation temperature blue spectrum concentration solar junction in GaInN/GaN

Abstract: Transparent wide gap junctions suitable as high temperature, high flux topping cells have been achieved in GaInN/GaN by metal-organic vapor phase epitaxy. In structures of 25 quantum wells (QWs) under AM1.5G illumination, an open circuit voltage of 2.1 V is achieved. Of the photons absorbed in the limited spectral range of <450 nm, 64.2% are converted to electrons collected at the contacts under zero bias. At a fill factor of 45%, they account for a power conversion efficiency of38.6%. Under concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…This rollover phenomenon in FF can be ascribed to the trade-off between carrier escape and recombination at high temperatures, which has also been identified in previous reports on InGaN/GaN MQW solar cells. 21,45 Finally, both devices showed the similar values and trends for V oc as shown in Fig. 6(d).…”
supporting
confidence: 63%
See 1 more Smart Citation
“…This rollover phenomenon in FF can be ascribed to the trade-off between carrier escape and recombination at high temperatures, which has also been identified in previous reports on InGaN/GaN MQW solar cells. 21,45 Finally, both devices showed the similar values and trends for V oc as shown in Fig. 6(d).…”
supporting
confidence: 63%
“…46 Consequently, the reference InGaN solar cell samples shared many similarities in PV performance with previous reports. 21,22,45 Nevertheless, InGaN solar cells with AlGaN layers completely outperformed the reference solar cell samples in almost every aspect of PV performance across the entire temperature range in measurements.…”
mentioning
confidence: 95%
“…Later, it was realized that the performance of InGaN solar cells can be further improved by utilizing strained InGaN quantum wells (QWs) or superlattice active layer structures, similar to the commercial III-nitride light-emitting diodes (LEDs). It was argued that these thin QW layers could mitigate defect formations that occur in thick InGaN layers and thus lead to improved device performance. With such an approach, single-junction InGaN QW solar cells with a relatively high external quantum efficiency of ∼50% and decent J sc and V oc were demonstrated. ,, Several groups also reported that the PV performance of InGaN QW solar cells can be reasonably sustained at high temperatures (e.g., 300 °C). Despite these encouraging progresses, these conventional InGaN solar cells unavoidably suffer from the polarization-related effects from the adoption of c -plane sapphire substrates, which have profound impacts on the efficiency of InGaN solar cells at both room temperature (RT) and high temperatures. At RT, the large polarization-induced electric field inside the InGaN/GaN QWs will lead to a large quantum barrier that hinders the carrier collection in solar cells. , At high temperatures, the polarization-related effects are convoluted with thermal escaping, making it even more challenging to probe, analyze, and engineer the carrier dynamics of InGaN solar cells.…”
mentioning
confidence: 99%
“…To date, high temperature operation of III-N devices has been theoretically predicted and experimentally demonstrated up to 600 C in air and 1000 C in vacuum. [24][25][26][27][28] For III-N InGaN solar cells, high efficiency operation at a temperature of 300 C has been demonstrated, [29][30][31][32] which is superior to traditional Si or III-V solar cells. Despite the promising results, very few studies on the thermal reliability of InGaN solar cells exist, and their degradation mechanisms at high temperature are still unclear.…”
mentioning
confidence: 99%